Emerging natural hydrocolloids : rheology and functions - Razavi, Seyed Mohammad Ali, 1967- (John Wiley & Sons, Inc., 2019)
"Hydrocolloids are a group of water-soluble naturally occurring polymers found abundantly in the nature. Some important functional properties of polysaccharide hydrocolloids are aqueous solubility, thickening, gelling, emulsion/foam stabilization ability, binding, interactions with the other hydrocolloids and sensory creation ability. The demand for natural food products is increasing among the health conscious consumer. This has resulted in the tremendous growth of the global hydrocolloids market. The global market for hydrocolloids is expected to reach a value of US$ 8,000 million by 2020 with a growing CAGR of 5.7%. The volume share of the ingredients depends on the security of their supply, quality and price. Hydrocolloids from plants have the advantage over those from animals because of their friendly image towards consumers. A lot of work has been carried out to characterize the chemical compositions and functional properties of many classic (commercial) hydrocolloids such as starch, pectin, xanthan, etc. However, there is still place in the hydrocolloid market for new sources of plant hydrocolloids to meet the demand for ingredients with more specific functionality in foods. And finally, health is still one of the biggest trends in the food industry. Many hydrocolloids are being investigated for their health benefits. They have been shown to reduce blood cholesterol levels, and many are a source of fibre, and may have prebiotic effects"--